Redesign of vaccine distribution networks. (2nd December 2019) - Lim, Jung; Norman, Bryan A.; Rajgopal, Jayant
Abstract: In most low‐ and middle‐income countries supported by the World Health Organization's Expanded Program on Immunization, vaccines are distributed through a legacy medical supply chain that is typically not cost‐efficient. Vaccines require storage and transport in a temperature‐controlled environment; this requires a "cold" distribution chain with capacity constraints on cold storage and cold transport. We propose an approach to redesigning the vaccine distribution chain that includes locating a set of intermediate distribution centers (DCs) and determining the flow paths from the central store (where vaccines are received into a country) through one or more of these to health clinics where vaccination actually occurs. In addition, the transport vehicles to allocate to each flow path, and the cold storage devices to use at each clinic or intermediate DC are determined. The redesigned network does not have to follow the current four‐tiered, arborescent structure commonly found in practice, but can use alternative network structures. To redesign this network optimally, we develop a mixed‐integer programming (MIP) model that can be used for small‐to‐medium‐sized problems and also present a hybrid heuristic–MIP method to obtain good solutions for larger problems. Numerical results are shown using data reflecting distribution networks in several countries in sub‐Saharan Africa.